2020
DOI: 10.1136/bmjopen-2019-032132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of point-of-care panel tests in ambulatory care: a systematic review and meta-analysis

Abstract: Strengths and limitations of this study ► This study was conducted robustly, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using a comprehensive search strategy in the major medical databases, and selection and quality assessment performed by two independent reviewers. ► It offers results on the impact of panel point-of-care tests (POCTs), rather than just their accuracy. ► Included studies were relatively small, and most notably for mortality, may be underpowered to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This is partly at odds with the concerns of emergency physicians who are willing to sacrifice some analytical quality for a faster TAT [ 9 ]. This can explain the craze for point-of-care testing (POCT) as an alternative to provide timely results, as it speeds up clinical decision making and relieves ED congestion by expediting patient flow [ 36 , 37 ]. However, there is still controversy about its ability to reduce the total ED-LOS [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is partly at odds with the concerns of emergency physicians who are willing to sacrifice some analytical quality for a faster TAT [ 9 ]. This can explain the craze for point-of-care testing (POCT) as an alternative to provide timely results, as it speeds up clinical decision making and relieves ED congestion by expediting patient flow [ 36 , 37 ]. However, there is still controversy about its ability to reduce the total ED-LOS [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of our scoping review was to provide an overview regarding the identified barriers and facilitators of POCT implementation in the international literature, as well as to summarize the involved managerial challenges focusing on the PC setting. Several systematic reviews covering different POCT clinical applications, GP attitudes, and economic evidence (Lingervelder et al, 2021;Goyder et al, 2020;Jones, 2013) have been published recently, thus we aimed to incorporate a broader overview of the implementation challenges and possible solutions regarding POCT in a PC setting.…”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that in European countries where POCT use is most prevalent at the GP level (specifically the Netherlands, Ireland, and the Scandinavian countries), first adapters who are also KOLs have recognized the diagnostic, therapeutic, and partly the economic benefits of POCT thus "paving" the path for subsequent adapters (Goyder et al, 2020). The cases of Australia and Canada are worth mentioning, where several key cost-effectiveness analyses have been published, and seem to be leading the way in POCT evaluation and evidence generation, hence the systematic spread and use of several POCT device in PC settings can be observed (Wong, et al, 2020;Lingervelder et al, 2021).…”
Section: Roadmapmentioning
confidence: 99%
“…shown to improve the speed with which AMI patients are identified. 34 Indeed the recent PROACT-4 133 trial, where POC troponin was tested in the ambulance setting, reported only modest time-savings 134 (0.3 hour) from first medical contact to discharge from ED or admission. 35 As no studies have 135 reported the impact of utilisation of POC hs-cTn assays in actual patient care (due to the newness of 136 this technology), our understanding of the effects of accelerated risk stratification on health systems 137 is also derived from reports using lab-based assays.…”
Section: Potential Role Of Poc Assays 129mentioning
confidence: 99%